Measuring severe stroke: a scoping review of RCTs - Roesner, Katrin; Brodowski, Hanna; Strutz, Nicole (Frontiers in Neurology, 2025)
BackgroundStroke severity affects length of hospital stay and functional recovery in rehabilitation. Therefore, establishing baseline data of stroke severity is a crucial step. In 2017, neurorehabilitation researchers met at the Stroke Recovery and Rehabilitation Roundtable (SRRR) to build a consensus on new standards for stroke recovery research. Core outcomes for measurement in stroke trials resulted in the recommendation that severe stroke should be assessed using the NIHSS. This scoping review aims to provide an overview of the variety of measurements used in clinical research to assess severe stroke.MethodsRCTs and CCTs were identified by searching PubMed, CENTRAL, SSCI, and ICTRP, covering articles published between January 2018 and September 2024. Peer-reviewed articles in English focusing on rehabilitative interventions and patients aged 18 years or older who have been classified with a severe stroke. The articles included were analyzed according to used measurements and cut-off scores.ResultsThe initial search yielded 1,004 publications, of which 35 (3.6%) studies were deemed eligible. In total, 11 different measures were used to assess severe stroke. Most studies used the NIHSS (n = 14), followed by mRS (n = 6), the FMA upper extremity (n = 4), the original FMA (n = 4) and the (modified) BI (n = 3). Seven different cut-off scores for the NIHSS were identified, with the scale being most frequently used in clinical settings.ConclusionThis review indicates substantial variability in measurements and a diverse range of cut-off scores. Consequently, comparability of patients’ baseline stroke severity across studies is limited. Given the fact that the NIHSS is only partially used, future efforts should focus on barriers and challenges using the NIHSS.